2002
DOI: 10.2337/diabetes.51.5.1425
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of L-Type Ca2+ Channels by Distinct Domains Within SNAP-25

Abstract: Cognate soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins are now known to associate the secretory vesicle with both the target plasma membrane and Ca 2؉ channels in order to mediate the sequence of events leading to exocytosis in neurons and neuroendocrine cells. Neuroendocrine cells, particularly insulin-secreting islet ␤-cells, t-SNARE proteins, 25-kDa synaptosomal-associated protein (SNAP-25), and syntaxin 1A, independently inhibit the L-type Ca 2؉ channel (L Ca ). Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 40 publications
3
48
0
Order By: Relevance
“…Because the t-SNAREs (syntaxin-1A and SNAP-25) also regulate rodent B-cell Ca 2ϩ (30) and K ϩ channels (voltage-dependent K ϩ -channel Kv2.1 and ATP-sensitive K ϩ channels) (31,32), which control the ionic events that trigger insulin exocytosis, perturbation of these ionic events by the reduced levels of SNARE proteins would contribute to the insulin secretory deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Because the t-SNAREs (syntaxin-1A and SNAP-25) also regulate rodent B-cell Ca 2ϩ (30) and K ϩ channels (voltage-dependent K ϩ -channel Kv2.1 and ATP-sensitive K ϩ channels) (31,32), which control the ionic events that trigger insulin exocytosis, perturbation of these ionic events by the reduced levels of SNARE proteins would contribute to the insulin secretory deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…SNARE proteins may therefore serve to orchestrate the sequence of ionic and exocytic events leading to secretion. Indeed, in the neuroendocrine islet beta cells, syntaxin 1A (Syn-1A) and SNAP-25 modulate voltage-gated Ca 2ϩ (10,11) and voltage-gated K ϩ channels (Kv2.1) (12). Recently, we have reported that Syn-1A also inhibits K ATP channels in pancreatic islet beta cells, through its actions on the NBF-1 of SUR1 (13).…”
mentioning
confidence: 99%
“…First, unlike the β cell Ca V 1.2 and Ca V 1.3 channels, which are tightly coupled to the exocytotic machinery (13)(14)(15), the Ca V 2.3 channel seems to be distant from the areas in the β cell where insulin-containing granules fuse with the plasma membrane and release their contents. Neither the deletion of the Ca V 2.3 subunit gene nor the pharmacological ablation of the Ca V 2.3 channel altered the exocytotic profile of insulincontaining granules from the immediately releasable pool.…”
Section: Figurementioning
confidence: 99%